Formal enantioselective synthesis of (-)-epiquinamide by proline-catalyzed one-pot sequential -amination/propargylation of aldehyde and asymmetric dihydroxylation of olefin - Ahuja, Brij Bhushan; Emmanuvel, Lourdusamy; Sudalai, Arumugam (Synlett, 2016)
Two independent routes to the formal synthesis of (-)-epiquinamide, have been described: the first route utilizes an l-proline-catalyzed one-pot sequential -amination/propargylation of aldehyde, while the second one employs asymmetric dihydroxylation as the key reaction to install the stereochemistry. While the first synthesis was accomplished in nine steps with 24.4% overall yield and dr 9:1, the second strategy resulted in the synthesis in eight steps with 36.4% overall yield and with perfect enantiocontrol.
Keywords: Amination; diastereoselective; Dihydroxylation; Proline; quinolizidine